The Effects of Work Stress on Employees Performance in the Banking Sector of Cameroon: Case of NFC Bank PLC Cameroon - Felici Banyi, Tabi; Grimbald, Ndah; Cornelius Wutofeh, Wuchu; Jong Ketuma, Henry (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The overall issue of stress management in National Financial Credit (NFC) Bank in Cameroon is so essential that it plays a critical role in ascertaining and ensuring a stress free financial services industry. It is the ultimate dream of every employer to have a stress free job environment. Thus having the right attitude to execute the job in order to increase productivity has not always been the case. The purpose of this study was to establish the relationship between the effects of work stress and job performance in the Cameroonian banking sector. Specifically, the study sought to explore the views of employees at National Financial Credit Bank regarding the issue of stress, its impact on employee performance and its management. Descriptive survey design was adopted as the most appropriate design for the study. The purposive and convenient sampling techniques were used to select all the heads of departments in the bank and the other bank employees for the study respectively. A sample of 50 respondents participated in the study. A questionnaire was designed based on a five point-likert Scale used in data collection. Five causal relationships were hypothesized and findings show that there was significant and positive correlation between employee performance and Work stress. Organizational level stress and group level stress as a mediating variable between individual level stress and work performance have a positive statistical significant effect on the performance of workers. This can be seen in table 13 (harmonized test of hypotheses) where the P_value for the stated hypotheses are significant within a 99% confidence interval level. The limitation of this study is that it was purely a quantitative based study. Future research should focus on using qualitative approaches to give an in-depth understanding on the causes of stress, the effects of stress and how stress management strategies can be designed to work. This study can offer useful information and insights for clarifying certain corporate concepts and can help to shape the development of future theory as well as the procedure for data collection and testing.